Time for a Paradigm Shift With Computerized Adaptive Testing of General Physical Function Outcomes Measurements. (January 2014) - Hung, Man; Franklin, Jeremy D.; Hon, Shirley D.; Cheng, Christine; Conrad, Jillian; Saltzman, Charles L.
Background: Patient-reported outcomes (PRO) are critical to understanding the value of orthopedic treatments. We hypothesized that use of the computerized adaptive testing from a well-characterized physical function item bank would show superiority in assessing all levels of physical function compared to current standard generic physical function outcomes instruments for foot and ankle patients. Methods: In a population of 126 foot and ankle patients we compared the psychometric properties for three PROs: the Physical Function subscale of the Medical Outcomes General Health Survey (SF-36 PF) version 2, the Patient-Reported Outcomes Measurement Information System (PROMIS) Physical Function (PF) Computerized Adaptive Test (CAT), and the Lower Extremity (LE) CAT. A Rasch item response theory (IRT) model was applied to assess and compare the fit, dimensionality, reliability, validity, and coverage. Results: The unexplained variance for the PF CAT was 3.9% and the LE CAT was 2.1%, suggesting each instrument explained a single concept. The SF-36 PF had more concerning unexplained variance of 7.6%. We found no floor or ceiling effects for the PF CAT, a minimal floor effect (1.6%) but no ceiling effect for the LE CAT, and an 11.1% floor effect and 9.5% ceiling effect for the SF-36 PF. Conclusion: Foot and ankle clinicians and researchers interested in measuring patient perceived functional outcomes with a generic instrument should consider using either the PF CAT or the LE CAT rather than the SF-36 PF. Further studies comparing these CATs to anatomic specific instruments are needed. Level of Evidence: Level I, diagnostic study.